In Memoriam of Editor Jennifer L. Gannon - Noé Lugaz; Delores Knipp; Steven K. Morley; Huixin Liu; Mike Hapgood; Brett Carter; Shasha Zou; Jiuhou Lei; Dan Welling (Space Weather)
Abstract Dr. Jennifer Gannon passed away suddenly on 2024 May 2 in Greenbelt, MD. Dr. Gannon had served as an editor for the Space Weather journal since April 2019, and she was the longest‐serving editor on the current board, having started under the previous editor‐in‐chief, Dr. Delores Knipp.